Two new species of the genus Pediculaster (Acari: Pygmephoridae) from Western Siberia, Russia - Khaustov, Alexander A. (Zootaxa, 2015)
Two new species of the genus Pediculaster Vitzthum, 1931 (Acari: Pygmephoroidea: Pygmephoridae), P. ermilovi sp. nov. and P. lignarius sp. nov. are described from rotten logs in Tyumen, Western Siberia, Russia. A key to phoretic females of Palaearctic species of the genus Pediculaster is provided.